2019
DOI: 10.1186/s12876-019-1057-2
|View full text |Cite
|
Sign up to set email alerts
|

Current diagnosis and management of Crohn’s disease in China: results from a multicenter prospective disease registry

Abstract: Background This study aimed to understand the disease characteristics and treatment outcomes of Crohn’s disease (CD) in a real-world setting in China. Methods In this prospective, non-interventional, multicenter disease registry, adults (≥18 years) with existing and newly diagnosed CD were recruited from 14 medical centers across China from January 2015 to January 2017. The study consisted of the enrollment and follow-up periods, of 12 months each. Demographic, clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 45 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…The reported mean or median age at diagnosis in those studies was mostly within the range of 20 to 40 years. [ 3 , 6 , 9 , 12 14 , 16 , 20 , 22 , 25 , 27 , 28 , 30 , 34 , 40 , 41 , 44 , 48 50 ] There was no gender preference in our cohort, which is similar to many cohorts from Western countries, [ 3 , 20 , 31 , 35 , 41 ] but most cohorts from Asia reported male predominance at 60% to 70%. [ 6 , 9 , 13 , 15 , 22 , 27 , 28 , 30 , 34 , 44 , 48 , 49 ] The locations of disease at diagnosis in our cohort were L3 (40%), L1 (35%), and L2 (25%).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The reported mean or median age at diagnosis in those studies was mostly within the range of 20 to 40 years. [ 3 , 6 , 9 , 12 14 , 16 , 20 , 22 , 25 , 27 , 28 , 30 , 34 , 40 , 41 , 44 , 48 50 ] There was no gender preference in our cohort, which is similar to many cohorts from Western countries, [ 3 , 20 , 31 , 35 , 41 ] but most cohorts from Asia reported male predominance at 60% to 70%. [ 6 , 9 , 13 , 15 , 22 , 27 , 28 , 30 , 34 , 44 , 48 , 49 ] The locations of disease at diagnosis in our cohort were L3 (40%), L1 (35%), and L2 (25%).…”
Section: Discussionsupporting
confidence: 73%
“…Although this duration is not nearly as long as the 3-year duration reported from India in 2009, [ 9 ] it is much longer than the median time to diagnosis of 3 months reported from Hong Kong and China in more recent years. [ 22 , 28 ] The median time to diagnosis in Europe was recently reported to be 4 months. [ 3 ] Furthermore, in contrast to the study from China that reported a dramatic decrease in the time to diagnosis from 79.4 months before 2010 to 3.1 months in 2015, [ 22 ] the diagnostic time in our study was stable between the before and after 2010 groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although this set of diagnostic criteria plays an important role in CD diagnosis in surgically resected bowel specimens, its sensitivity and speci city have not been investigated. The incidence of CD has been steadily increasing in China in recent years [3]. Large-scale multicenter studies examining the diagnostic sensitivity and speci city are needed to validate the above diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%